Effect of Host Tree Seasonal Phenology on Substrate Suitability for the Pine Engraver (Coleoptera: Scolytidae): Implications for Population Dynamics and Enemy Free Space. Issue 4 (4th September 2014) - Redmer, Jacqueline S.; Wallin, Kimberly F.; Raffa, Kenneth F.
Abstract : This study evaluated the effects of seasonal phenology on the substrate quality of susceptible hosts to the pine engraver, Ips pini (Say). We also determined the effects of the duration and method of storage on host quality for purposes of laboratory rearing. Live red pine trees were felled at various times during the season, and I. pini adults from a laboratory colony were established on the logs. Subsamples of logs were stored for various intervals, and then provided to beetles. Subsamples of stored logs were waxed at both ends to prevent water loss before being submitted to the same assays. Suitability of red pine phloem tissue in susceptible hosts declined for I. pini throughout the growing season. As the season progressed, the number of beetle progeny that emerged from colonized hosts dropped substantially. This decline was associated with simultaneous reductions in phloem moisture content. Reduction in host suitability may partially offset any advantage I. pini may gain from colonizing trees after the major predators have become less abundant. Bark beetle brood production decreased significantly with length of storage, regardless of the month of tree felling or the method of storing. Implications for bark beetle population dynamics and laboratory rearing systems are discussed.